Relationship between sRAGE and hsCRP as Markers of Cardiovascular Disease Risk Factors in Diabetic and Non-Diabetic Men with Central Obesity - Rambu Beppy Hamuaty; Indriyanti Rafi Sukmawati; Ferry Sandra (Cell and BioPharmaceutical Institute, 2017)
Background: Interaction between advanced glycation end product (AGE) and receptor for AGE (RAGE) triggers the escalation of inflammatory cytokine expressions. High-sensitivity C-reactive protein (hsCRP), an important inflammatory marker, has been reported to be modulated by soluble RAGE (sRAGE). However, the relationship between hsCRP and sRAGE in diabetes was not clearly described. Therefore present study was conducted to determine the relationship between sRAGE with hsCRP in men with central obese diabetic and non-diabetic. Materials and Methods: Adult men aged 25-60 years with central obese diabetes and non-diabetes, were recruited. Patient’s profiles were collected before the physical and blood examination. Physical examinations were conducted by measuring waist/abdomen, blood pressure, height, and weight. The routine blood test was performed to obtain concentrations of fasting blood glucose, HbA1c, hsCRP and sRAGE level.Results: Fifty-seven subjects with central obese and waist size ≥90 cm were selected. It was found that hsCRP values were significantly different (p=0.000) in HbA1c <6.5% dan HbA1c ≥6.5% groups. There was an inverse relationship between hsCRP and sRAGE levels for both in HbA1c <6.5% (r=-0.073) and HbA1c≥6.5% (r=-0.022) groups. In HbA1c ≥6.5% group, sRAGE showed strong positive correlation with 1 mg/dL ≤ hsCRP <3 mg/dL group (r>0.5).Conclusions: In the early stages of diabetes with hsCRP <1 mg/dL, the protective function was demonstrated with greater sRAGE levels. However, in further phase with 3 ≤ hsCRP < 10 mg/dL, the level of sRAGE was low, which is assumed to be associated with complications. Hence, sRAGE could be suggested as a complementary marker for hsCRP to evaluate diabetic men with central obesity.Keywords: sRAGE, hsCRP, diabetes, HbA1c, central obesity